Health perceptions of patients with forgotten double-J stent - Ogras,Mehmet Sezai; Yildirim,Kadir (PeerJ, 2024)
Aim In this article, we aimed to determine the health perceptions of the patients who did not apply for double-J stent (DJS) removal on time and evaluate whether health perceptions impact this behavior. Materials and Methods Health perceptions of 22 patients who were treated for forgotten double-J stent (FDJS) between January 2017–October 2020 and 25 patients who applied for DJS removal during the given appointment time in the urology department of Elazig Training and Research Hospital and Elazig Fethi Sekin City Hospital were compared using the “Health Perception Scale”. Results Health perception scale scores in the FDJS group and control group were 62-68 (mean = 64.27 ± 1.75) and 63-68 (mean = 65.36 ± 1.55), respectively. With regard to the sub-factors of the scale, control center scores were 21.86 ± 0.77 and 22.08 ± 1.15; precision scores were 16.54 ± 0.80 and 16.56 ± 0.82; importance of health scores were 12.77 ± 0, 92 and 13.32 ± 0.74; and self-awareness points were 13.04  ± 0.72 and 13.48 ± 0.58, respectively. There was a statistically significant difference between the health perception scale in total, importance of health, and self-awareness scores between the two groups. At the same time, there was no difference in terms of the control center and precision scores (p∗ = 0.029, p∗ = 0.030, p∗ = 0.028, p = 0.460, p = 0.951). Conclusion Patients’ and their families’ educational status, income levels and lack of follow-up by healthcare professionals play an important role in forgotten DJS cases and patients’ perception of health may also have an impact on this behavior.
Keywords: Health; Perceptions; Forgotten; DJS